Evaluating the Functional Outcomes and the Quality of Life for Pediatric Patients with Osteogenesis Imperfecta after Fracture Treatment with Intramedullary Rodding - Alexandru Herdea (MDPI AG, 2021)
Background and Objectives: Osteogenesis imperfecta is a rare pathology involving the bones and the connective tissues, generating alterations that lead to frequent fractures during childhood. When fractures occur at birth, they are associated with an impairment of walking and the quality of life. Although surgical techniques have significantly improved in recent years, functional outcomes and the quality of life for pediatric patients that benefited from surgical management with telescopic rods have been less evaluated. This study aimed to measure functional results and determine the factors that influence the quality of life for the pediatric population diagnosed with Osteogenesis imperfecta and surgically treated using the telescopic rod approach after suffering a fracture or severe deformity. Materials and Methods: We conducted a cohort study that consisted of 15 patients diagnosed with Osteogenesis imperfecta (average age of 11.6 years). All individuals possessed at least one intramedullary telescopic rod as a result of the surgical treatment. Results: We observed that the pain, both acute and chronic, impairs the quality of life and interferes with daily living activities, for instance, self-care tasks. Conclusions: Osteogenesis imperfecta is associated with a severely damaged level of walking. All of the aspects of the pediatric patient’s daily life activity seem to be affected. Furthermore, these patients, especially those residing in rural areas, have a poor quality of life.